Perbandingan Kelengkapan Resep Konvensional Dengan Resep Berbasis Online Di Apotek X Wilayah Denpasar Selatan - Dhiancinantyan Windydaca Brata Putri; Nyoman Titin Brimantari; I Ketut Tunas (UNIVERSITAS MUHAMMADIYAH MATARAM, 2023)
One of the pharmaceutical services is to serve the completeness of prescriptions served in health services such as pharmacies. The completeness of prescription services at online-based pharmacies is still carried out by pharmacists but is limited in nature. As a result of incomplete prescription writing, medication errors can occur which are detrimental to the patient (Isro et al., 2018). This study aims to determine the difference in the completeness of conventional recipes with online-based recipes. This study used an analytical observational design, with a cross-sectional study design, and the sampling method was carried out using purposive sampling technique, so that 50 conventional recipes and 50 online recipes were obtained. Based on the results of research conducted at the south Denpasar pharmacy. The results of the study in the form of administrative, pharmaceutical, clinical studies of conventional prescriptions and online prescriptions can be seen in terms of indicators of patient age, doctor's name, No. Doctor's SIP, doctor's initials, R/ sign, dosage form, dosage strength, drug dose, and drug allergy P Value 0.05. Then in terms of indicators of weight px, address px, date of prescription, and drug rules, the value of P Value is 0.05. So, it can be concluded that there is a significant difference between the completeness of conventional prescriptions and online prescriptions in terms of age px, doctor's name, SIP No. , doctor's initial, R/ sign, dosage form, dosage strength, drug dose, and allergy.